2011
DOI: 10.1097/ta.0b013e3181edc80e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Arm Positioning on Radiation Dose for Whole Body Computed Tomography in Trauma Patients

Abstract: Based on our retrospective investigation, it can be recommended with reference to whole body computed tomography screening that the arms should be in the arms-up position during thorax or abdomen scanning of a severely injured patient, provided there are no clear clinical indications of shoulder injury. For the patient, this position is associated with a significantly reduced radiation dose without noticeable loss of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 28 publications
2
23
1
1
Order By: Relevance
“…26 The scan protocols published have been heterogeneous in terms of scan parameters, which have been adjusted to the institutional needs of image quality and patients' characteristics. However, comparable scan protocols resulted in a drop of the mean effective dose of 21.2-24.69 mSv, 27,28 which is similar to our result of 24.4 mSv with FBP.…”
Section: Discussionsupporting
confidence: 80%
“…26 The scan protocols published have been heterogeneous in terms of scan parameters, which have been adjusted to the institutional needs of image quality and patients' characteristics. However, comparable scan protocols resulted in a drop of the mean effective dose of 21.2-24.69 mSv, 27,28 which is similar to our result of 24.4 mSv with FBP.…”
Section: Discussionsupporting
confidence: 80%
“…Brink et al [13] reported an additional dose of 8 mSv when placing the arms alongside the body as compared to raising the arms above the head, and proposed the latter arm repositioning as a tool for optimizing the dose-benefit ratio of CT in polytrauma patients. Bayer et al [14] showed that radiation dose significantly increases if the arms were placed alongside the body and not elevated above the head, reporting average effective dose values of 24.7 mSv (arms alongside the body) and 19.2 mSv (arms above the head), respectively. Having evaluated the data of 276 whole-body trauma CT scans, Baskerville et al [27] reported mean CTDI vol values from 77 to 115 mGy for thoraco-abdominal data acquisitions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be considered that many trauma patients are fairly young, and care needs to be taken in designing and adapting the CT scanning protocols to minimize and optimize radiation exposure [20][21][22][23]. One issue related to radiation exposure of whole-body CT is the positioning of the patient's arms [13,14]. Some authors suggested elevating the arms above the head after scanning of the head and cervical spine, before performing thoracoabdominal CT [4,12,14,18], whereas others suggest leaving the arms alongside the body for time gain [7,15,16,24] and prevention of iatrogenic injuries [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations